Intra-European litigation in eighteenth-century Izmir - Vanneste, Tijl. (Leiden ; Boston)
xi, 366 sayfa
Keywords: “Scholars have long debated the use of law to settle international trade disputes in the early modern period. In this book, Tijl Vanneste uses the case study of commercial litigation before the Dutch consular court of Izmir to argue that merchants relied on a particular blend of mercantile customs, which he calls 'the merchants' style', and specific legal forms and procedures, laid down in written regulations, and dependent on local and international circumstances. The book challenges the idea of a universal 'law merchant', to replace it with a more nuanced analysis that centralizes the interplay between informal merchant custom, as advocated by traders and judges alike, and formal procedural legislation, drawn mostly from Roman law, in the resolution of mercantile disputes.” --